Adjunctive statin therapy reduces intracranial hemorrhage and 1-year mortality in patients with atrial fibrillation after acute ischemic stroke: A population-based epidemiological study from Taiwan. (November 2019) - Lin, Hui-Chen; Tsai, Wan-Chen; Lin, Jr-Rung; Chang, Wen-Neng; Huang, Chih-Cheng; Wang, Hung-Chen; Kung, Chia-Te; Su, Chih-Min; Su, Yu-Jih; Lin, Wei-Che; Cheng, Ben-Chung; Lu, Cheng-Hsien; et al.
Highlights: Statin therapy reduce the risk for ICH in AF patients after AIS. Statin treatment reduce one-year mortality in AF patients after AIS. The effect of statin therapy on recurrent stroke is not remarkable in AF patients. Abstract: Background: Atrial fibrillation (AF)-related stroke causes severe disability and poor prognosis. Adjunctive statin therapy has been recommended for atherosclerotic-related stroke but not AF-related stroke. This study investigated the effects of statin in AF patients who experienced acute ischemic stroke. Methods: Data from patients with AF experiencing first-ever ischemic stroke between 2001 and 2010 were collected from the Taiwan National Health Insurance Research Database and categorized into non-statin and statin groups. The statin group was further divided into pre-stroke statin (those who began statin therapy before stroke) and post-stroke statin (those who began statin therapy after stroke) groups. The risks for recurrent ischemic stroke, coronary artery disease (CAD), intracranial hemorrhage (ICH), and 1-year mortality were compared among the groups. Results: A total of 43, 242 patients were in the non-statin, 2858 in the pre-stroke statin and 4640 in post-stroke statin groups. Comparing the risk for recurrent stroke and CAD among the three groups, the pre-stroke statin and post-stroke statin groups did not exhibit a significant difference compared with the non-statin group. In terms of ICH risk, the statin group had a lower risk for ICH (odds ratio [OR] 0.79, 95% confidence interval [CI] 0.68–0.90; p = 0.0007) compared with the non-statin group. The overall 1-year mortality in both statin subgroups was lower than that in the non-statin group (pre-stroke statin, OR 0.55 [95% CI 0.49–0.61]; p < 0.0001 versus post-stroke statin, OR 0.53 [95% CI 0.48–0.58]; p < 0.0001). Conclusions: Statin therapy reduced the risk of ICH and 1-year mortality in AF patients who experienced acute ischemic stroke.